Quantitative disentanglement of nanocrystalline phases in cement pastes by synchrotron ptychographic X-ray tomography - Cuesta-García, Ana María; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Díaz, Ana; Trtik, Pavel; Holler, Mirko; Lothenbach, Barbara; García-Aranda, Miguel Ángel (IUCr, 2019)
Mortars and concretes are ubiquitous materials with very complex hierarchical microstructures. To fully understand their main properties and to decrease their CO2 footprint, a sound description of their spatially resolved mineralogy is necessary. Developing this knowledge is very challenging as about half of the volume of hydrated cement is a nanocrystalline component, calcium silicate hydrate (C-S-H) gel. Furthermore, other poorly crystalline phases (e.g. iron siliceous hydrogarnet or silica oxide) may coexist, which are even more difficult to characterize. Traditional spatially resolved techniques such as electron microscopy involve complex sample preparation steps that often lead to artefacts (e.g. dehydration and microstructural changes). Here, synchrotron ptychographic tomography has been used to obtain spatially resolved information on three unaltered representative samples: neat Portland paste, Portland–calcite and Portland–fly-ash blend pastes with a spatial resolution below 100 nm in samples with a volume of up to 5 x 104 mm3. For the neat Portland paste, the ptychotomographic study gave densities of 2.11 and 2.52 g cm -3 and a content of 41.1 and 6.4 vol% for nanocrystalline C-S-H gel and poorly crystalline iron siliceous hydrogarnet, respectively. Furthermore, the spatially resolved volumetric mass-density information has allowed characterization of inner-product and outer-product C-S-H gels. The average density of the inner-product C-S-H is smaller than that of the outer product and its variability is larger. Full characterization of the pastes, including segmentation of the different components, is reported and the contents are compared with the results obtained by thermodynamic modelling.
Keywords: Cemento Portland; Rayos X, Análisis por; Microestructura; Densidad-Medición; Tomografía; Termodinámica; Portland cement; X-ray imaging; microstructure determination; density measurements; C-S-H gels; amorphous hydrogarnet; synchrotron ptychographic tomography; nanocrystalline components; thermodynamic modelling